USING INTERACTIVE MEDIA OF SPOTIFY IN LISTENING COMPREHENSION FOR STUDENTS IN INTENSIVE ENGLISH COURSE OF LANGUAGE CENTER IN UNIVERSITAS MUHAMMADIYAH SURABAYA - Waode Hamsia; Roifah Roifah (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
Listening is one of the important activities in learning that can obtain information. Based on the phenomenon that students have difficulty in learning English, especially in listening skills because many students have difficulty in listening comprehension clearly. Moreover, they feel bored because of the teaching and learning process without using interactive media. The purpose of this research found out the implementation of the listening comprehension learning process in intensive English class of the Language Center by using the Spotify media as an interactive learning media and students' responses in using of the Spotify media.   The researchers used three instruments in this research that were observation, questionnaire, and interview. Qualitative method was used by researchers to analyze descriptive data. The results showed that the students were interested when the lecturer used the Spotify media as part of the teaching and learning process. Furthermore, the students responded positively to the use of the Spotify media. The results of the analysis showed that the using of Spotify media by the lecturer in the learning process of listening to understanding is very pleasant and students are easier to understand English in listening skill. Since they can use the Spotify anywhere and anytime that was as the new experience in learning English for their daily activities